Therapeutic resistance training: proposal for an algorithm-based approach - Weber Frank; Stark Christina; Bloch Wilhelm; Böcker Jonas; Drey Michael; Gehlert Sebastian; Maier Björn; Peters Kirsten; Sachs Ludwig; Schoser Benedikt; Schönau Eckhard; Schröder Rolf; et al. (Translational Exercise Biomedicine, 2024)
Ageing, immobilization, sepsis or cachexia reduce muscle mass and function. The age-related loss, i.e. sarcopenia, contributes to frailty and results in a loss of mobility and autonomy in aging and disease. Affected individuals are often socially isolated, have a greater risk of metabolic disorders and psychosomatic problems. As a result, quality of life and life expectancy are affected. Immobilization and lack of adequate stimuli to the skeletal muscle seem to play a central part in these problems. To overcome them, resistance training (i.e., weightlifting) is an effective intervention.